Measurement of Value in Anterior Cruciate Ligament Reconstruction: Patient-Level Value Analysis for the two-year Episode of Care. Issue 7 (31st July 2020) - Parikh, Harsh; Flagstad, Ilexa; Reams, Megan; Tompkins, Marc; Nelson, Bradley; Cunningham, Brian; Siljander, Breana
Objectives: Value-based payment models attempt to incentivize healthcare practices that reduce costs while improving patient outcomes. In order to optimize value, orthopaedic practices need a mechanism to quantify the value of the care that is provided to each individual patient. While this concept has been applied to total joint arthroplasty, sports has been largely excluded. Patient-level value-analysis (PLVA) defines value as a patient's outcome achieved divided by the total cost of their episode of care. Measuring value on the patient-level allows a single number to describe value of the care received. The purpose of this study is to report PLVA and measure factors that influences the value of care delivered. Methods: All patients that underwent an ACL reconstruction for an acute ACL tear between the years of 2009 and 2016 at a single outpatient orthopaedic surgery center were identified via retrospective review of a prospectively collected patient-reported outcomes (PROs) registry. Patient demographics were collected via the electronic medical record (EMR) (Figure 2). The episode of care was defined as 2 years after surgery. The knee osteoarthritis outcomes score (KOOS) system was collected at initial preoperative baseline and two-years following surgery. The total cost-of-care was determined using time-driven activity-based-costing (TDABC). This formula derives the cost of care as a function of the time spent for each activity and personnel cost contributions for all involved. This process was performed at all phases: surgical intervention, all clinical follow-ups, and physical therapy (PT) sessions. Results: A total of 611 patients were included for this investigation. The patient sample was primarily female (n=355, 58.1%), average age of 28.9 + 12.9 [27.9, 30.0], and average BMI of 25.5 + 4.5 [25.2, 25.9]. A total of 151 (24.7%) patients were treated with an allograft with 128 (84.8%) utilizing a bone-patellar-bone (BTB) graft source. A total of 460 (75.3%) patients were treated with autograft with 272 (59.1%) utilizing a BTB graft source. The KOOS score was 65.3 + 15.9 [63.6, 66.9] at baseline and 83.2 + 13.5 [81.8, 84.6] at two-years, representing an improvement of 17.9 + 16.8 [16.2, 19.7]. There was a poor correlation between the change in two-year KOOS score and the TDABC cost-of-care (r=0.11). Autograft BTB demonstrated the highest overall value at two-years, 0.74 (ANOVA F: p<0.01), with an estimated 64.3% of patients falling in the "Above Average + Low Cost, " quadrant (Figure 1). Conclusion: This is the first study to apply PLVA methodology over the entire episode of care for ACL reconstructions. In our study, there was no correlation between an increased cost-of-care and an improvement in patient-reported outcomes. The autograft BTB demonstrated the greatest patient-level value within this cohort. With the growing focus of healthcare transitioning towards value-based delivery, PLVA offers orthopaedic practices and healthcare institutions a quantitative framework to evaluate the value of individual patient care delivery over the entire episode of care. This data can be utilized to drive physician behavior change, develop better care pathways, and optimize care delivery. Figure 1. Figure 2.